Is Iron Deficiency Anemia a Risk Factor in Asthmatic Children? - Nadia M. Fida; Haya Z. Kamfar (Journal of King Abdulaziz University: Medical Sciences, 2023)
Asthma, a common problem worldwide with numerous risk factors; yet, few researchers mentioned iron deficiency anemia as a risk factor. This study evaluates prevalence of iron deficiency anemia among asthmatic children and adolescents. A cross sectional study conducted among patients attending asthma clinics at King Abdulaziz University Hospital, Jeddah, Saudi Arabia from January 2008 June 2009. 117 children (0.7-15-years-old) were included in the study. All participants were subjected to complete history, clinical examination, laboratory and imaging investigations. Serum iron and ferritin were estimated using ELISA kits. According to complete blood count, asthmatic patients were divided into patients with iron deficiency anemia [19.70% (n = 23)] and without iron deficiency anemia [80.30% (n = 94)]. In all asthmatic patients; low values were found for hematocrit (41.0%); mean corpuscular volume (41.9%) and hemoglobin (17.9%); platelets (0.9%); iron (5.1%); ferritin (12.0%), while high value was found for red cell distribution width (31.6%). In asthmatic patients with iron deficiency anemia; mean corpuscular hemoglobin, platelets count, iron and ferritin were significantly lower than those without anemia. The prevalence of iron deficiency anemia in asthmatic patients was 19.70%. In conclusion, iron deficiency anemia needs to be considered as a risk factor in asthmatic patients.